PHYSICAL PROPERTIES OF LIQUID FE ALLOYS AT HIGH PRESSURE AND THEIR BEARINGS ON THE NATURE OF METALLIC PLANETARY CORES - Sanloup C.; Gillet P.; Guyot F.; Fei Y. (My University, 2002)
Sulfur and silicon are among the expected alloying light elements in planetary liquid iron cores. Structural properties of Fe-27 wt % S and Fe-17 wt % Si liquid alloys at high pressure and high temperature (0-5 GPa/1400-2300 K) are measured by synchrotron X-ray diffraction. Sulfur strongly modifies the local structure of liquid iron whereas silicon has only small structural effects. Fe-27 wt % S melts are indeed poorly ordered which explains a higher compressibility compared to pure liquid Fe. These results point out the necessity to consider the strong effect of S on liquid Fe properties while modeling planetary interiors. They imply a low S content in the Earth's outer core, leaving Si as a strong candidate, and argue for a present-day Martian solid core when combined with previous global chemical models.
Keywords: core; liquid; iron; X-rays; Mars; Ganymede